Desarrollo y ciudadanía: la resiliencia de las comunidades rurales en Pasco y Huánuco pos conflicto armado en el Perú - Meza Salcedo, Américo (2020)
Objective: to analyze the way in which the rural communities of Pasco and Huánuco strengthen the family bond and the community organization post armed conflict. Methodology: the research was qualitative and the design of ethnographic and hermeneutical research. The fieldwork was developed with participatory observation and structured interview. The unit of analysis was formed by community leaders and leaders living in both areas, victims of the internal armed conflict. Results: based on the data collected in the field, it can be inferred that the victims managed to overcome the trauma of the past lived. Although a group of them have not yet found the bodies of their relatives, disappeared after extrajudicial executions by members of the Army, they hope that this reality will be consummated soon, so that they can close the circle of violence and give them a Christian burial To their dead. Conclusion: the victims employed personal, family and social strategies to cope with the pain generated by the internal armed conflict, migrate to another place and resume their life project; in particular, for their children to continue their studies and look to the future with optimism.   DOI:  https://doi.org/10.31876/sl.v4i1.48